2015
DOI: 10.1080/01635581.2016.1105267
|View full text |Cite
|
Sign up to set email alerts
|

Cancer chemoprevention research with selenium in the post-SELECT era: Promises and challenges

Abstract: The negative efficacy outcomes of double-blinded, randomized, placebo-controlled Phase III human clinical trials with selenomethionine (SeMet) and SeMet-rich selenized-yeast (Se-yeast) for prostate cancer prevention and Se-yeast for prevention of non-small cell lung cancer (NSCLC) in North America lead to rejection of SeMet/Se-yeast for cancer prevention in Se-adequate populations. We identify two major lessons from the outcomes of these trials: 1) The antioxidant hypothesis was tested in wrong subjects or pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 101 publications
(145 reference statements)
0
42
0
1
Order By: Relevance
“…No other bioselenocompounds induced the cell proliferation. MeSeCys is a promising agent in cancer prevention and treatment [19]. It is reported that S -methylcysteine (MeCys) exerts a chemopreventive effect [20].…”
Section: Discussionmentioning
confidence: 99%
“…No other bioselenocompounds induced the cell proliferation. MeSeCys is a promising agent in cancer prevention and treatment [19]. It is reported that S -methylcysteine (MeCys) exerts a chemopreventive effect [20].…”
Section: Discussionmentioning
confidence: 99%
“…Se can potentially help in switching the arachidonic acid pathway from pro-inflammatory expression to anti-inflammatory responses and reduce the risk of cancer (Lu et al, 2015), arthritis (Onal, Naziroglu, Colak, Bulut, & Flores-Arce, 2011), and other cardiovascular diseases (Bukkens et al, 2013). In recent past, our group has been reported the significant hyperaccumulation of Se in staple crops ranging from 20 to 123 µg/g in wheat, maize and rice matrices (Dhanjal, Sharma, & Nagaraja, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Intake and status of selenium in most European countries are relatively low as compared to the USA [10, 12]. This supports further exploration of the role of selenium for prostate cancer prevention in these populations with marginal selenium status [11]. Rather than initiating another large intervention trial, we advocate to first gain further insight into the mechanisms underlying the role of selenium in cancer biology and other health related outcomes.…”
Section: Introductionmentioning
confidence: 87%